2014
DOI: 10.1007/978-3-642-54423-1_47
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of Coloring Graphs without Paths and Cycles

Abstract: Abstract. Let Pt and C denote a path on t vertices and a cycle on vertices, respectively. In this paper we study the k-coloring problem for (Pt, C )-free graphs. Maffray and Morel, and Bruce, Hoang and Sawada, have proved that 3-colorability of P5-free graphs has a finite forbidden induced subgraphs characterization, while Hoang, Moore, Recoskie, Sawada, and Vatshelle have shown that k-colorability of P5-free graphs for k ≥ 4 does not. These authors have also shown, aided by a computer search, that 4-colorabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(57 citation statements)
references
References 26 publications
4
53
0
Order By: Relevance
“… proved that 4‐ Precoloring Extension is sans-serifNP‐complete for (C7,P8)‐free graphs, which implies (ii):4, and they also proved (ii):7. We observe that (ii):2, (ii):3, and (ii):5 follow immediately from corresponding results for k ‐ Coloring as shown by Hell and Huang . Finally, we consider k ‐ Coloring ; first the sans-serifNP‐complete cases.…”
Section: Results and Open Problems For (H1h2)‐free Graphssupporting
confidence: 74%
See 1 more Smart Citation
“… proved that 4‐ Precoloring Extension is sans-serifNP‐complete for (C7,P8)‐free graphs, which implies (ii):4, and they also proved (ii):7. We observe that (ii):2, (ii):3, and (ii):5 follow immediately from corresponding results for k ‐ Coloring as shown by Hell and Huang . Finally, we consider k ‐ Coloring ; first the sans-serifNP‐complete cases.…”
Section: Results and Open Problems For (H1h2)‐free Graphssupporting
confidence: 74%
“… proved that the Grötzsch graph is the only 4‐critical (C3,P6)‐free graph. Hell and Huang showed that, for all k1, the number of k ‐vertex‐critical (C4,P6)‐free graphs is finite. Moreover, they gave an explicit construction of all four 4‐vertex‐critical (C4,P6)‐free graphs and of all 13 5‐vertex‐critical (C4,P6)‐free graphs.…”
Section: Results and Open Problems For (H1h2)‐free Graphsmentioning
confidence: 99%
“…Very recently, Hell and Huang [16] extended the results in Table 2 by showing that k-COLORING is NP-complete on (C r , P )-free graphs in the following cases:…”
Section: Our Resultsmentioning
confidence: 99%
“…The aforementioned results of Hell and Huang [16], which improve the results in Table 2, combined with our result for k = 4, r = 3 and = 164 and the known polynomial-time results for k-COLORING on P -free graphs (namely the cases k ≥ 1, ≤ 5 [17] and k = 3, = 6 [31]) leave a number of cases open in the computational complexity classification of k-COLORING for (C r , P )-free graphs. An intriguing question is to determine the computational complexity of 3-COLORING restricted to (C 3 , P )-free graphs for all integers .…”
Section: Future Workmentioning
confidence: 89%
“… have shown that the only 4‐critical (P6,C3)‐free graph is the Grötzsch graph. More recently, Hell and Huang proved that there are four 4‐critical (P6,C4)‐free graphs. They also proved that in general, there are only finitely many k ‐critical (P6,C4)‐free graphs.…”
Section: Introductionmentioning
confidence: 99%